Tuning the chemistry of seawater with activated clay: an application in SmartWater enrichment for enhanced oil recovery - Jimoh K. Adewole; Taye S. Kazeem; Tajudeen A. Oyehan (Journal of Petroleum Exploration and Production Technology, 2020)
Abstract Studies on the interaction between crude oil, brine, and rock systems showed that the composition of water injected into the oil reservoir influences the amount of oil recovered from such a reservoir. Therefore, researchers are now emphasizing the use of SmartWater for enhanced oil recovery (EOR). In this research, the capability of activated clay to be used for tuning the chemistry of seawater for subsequent production of SmartWater was investigated. Filter cakes were formed using bentonite and its blends with raw clay and activated clay (which was produced in-house using locally obtained clay samples). The capability of the cakes to control the transport properties of permeating seawater was evaluated in terms of ion rejection. The average rejection for the raw clay cake for Na+, K+, Mg2+, and Ca2+ is 4.45, 49.64, 53.33, and 94.43%, respectively. The rejection results for the mixed-matrix cake containing the activated clay were 6.38, 51.34, 86.19, and 78.09 for Na+, K+, Mg2+, and Ca2+, respectively. It was observed that the selectivity of the filter cake for Mg2+ and Ca2+ was reversed due to the addition of the activated clay. Thus, activated clay possesses some potentials for SmartWater production for an EOR application.